2018
DOI: 10.2147/ijgm.s176493
|View full text |Cite
|
Sign up to set email alerts
|

Relapsing fever <em>Borrelia</em> in California: a pilot serological study

Abstract: BackgroundBorrelia spirochetes are tick-borne Gram-negative bacteria that cause disease in humans and animals. Although many studies have focused on Borrelia burgdorferi (Bb), the agent of Lyme disease, recent studies have examined the role of Relapsing Fever Borrelia (RFB) in human disease. In this pilot study, we have evaluated serological reactivity against Bb and RFB in patients residing in California.MethodsSerological testing for reactivity to Bb and RFB antigens was performed in 543 patients with suspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 38 publications
(46 reference statements)
2
19
0
Order By: Relevance
“…Although the ecology and epidemiology of RFB in Africa is well described [13], advances in molecular testing led to widespread identification of Borrelia spp. in human specimens, thus challenging prevailing thought regarding geographic distribution and prevalence of RFB infection [15]. For example, a recent study reported that approximately 23% of a cohort of 301 patients in Russia with confirmed Borrelia infection demonstrated positive molecular testing for B. miyamotoi [31].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the ecology and epidemiology of RFB in Africa is well described [13], advances in molecular testing led to widespread identification of Borrelia spp. in human specimens, thus challenging prevailing thought regarding geographic distribution and prevalence of RFB infection [15]. For example, a recent study reported that approximately 23% of a cohort of 301 patients in Russia with confirmed Borrelia infection demonstrated positive molecular testing for B. miyamotoi [31].…”
Section: Discussionmentioning
confidence: 99%
“…The genetic diversity of Borrelia spirochetes, as well as the symptoms of infection that are as diverse as the organisms causing them, makes it challenging to diagnose Borrelia-associated disease [15,43]. It is important to recognize that classification is a human concept and the organisms encompassing the genus Borrelia fall within a continuous spectrum of organisms rather than into well-defined genetically distinct groups that are easily categorized.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations